BAHASA MATEMATIKA SEBAGAI STRATEGI RETORIS DAKWAH DIGITAL: ANALISIS METAFORA KONSEPTUAL PADA KONTEN TIKTOK - Insani, Camelya Nurul; Ramadhan, Salbana Ziadatul; Sri Rahayu, Alleya Danti; Al Aziz, Fathurrohman; Pertiwi, Attin Rahmah; Putri, Amalia Azizah; Huda, Shohibul; Nurdiansyah, Muhamad Iqbal; Sulistyani, Anjar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study analyzes the use of mathematical language as a creative communication strategy in Islamic da'wah content on social media, particularly TikTok, among Generation Z audiences. Using a qualitative descriptive approach with qualitative content analysis based on Krippendorff's (2019) framework, this research examined seven TikTok uploads that explicitly employed mathematical terms or symbols (numbers, arithmetic operators, or words such as "formula" or "logic") in religious contexts. The data were purposively sampled and coded based on Kövecses's (2005) classification of conceptual metaphors: structural, orientational, and ontological. The findings reveal that six of the seven uploads employed structural metaphors, divided into two rhetorical patterns: (1) reversing conventional arithmetic logic to represent boundless reward and sincerity (five uploads), and (2) affirming valid mathematical relations as rational proof of monotheism (one upload). One upload employed an ontological metaphor, concretizing the abstract concept of selective religious practice through a "food stall" analogy. No orientational metaphors were found in the collected data. These findings suggest that mathematical language in digital da'wah functions as a deliberate rhetorical strategy that bridges rational logic familiar to Generation Z with abstract spiritual concepts, and that such analogies have developed into a recurring rhetorical formula across different content creators.